2022
DOI: 10.3390/pharmaceutics14020390
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticle-Based Drug Delivery Systems for the Treatment of Pancreatic Cancer: A Systematic Literature Overview

Abstract: Pancreatic cancer is a devastating disease with the worst outcome of any human cancer. Despite significant improvements in cancer treatment in general, little progress has been made in pancreatic cancer (PDAC), resulting in an overall 5-year survival rate of less than 10%. This dismal prognosis can be attributed to the limited clinical efficacy of systemic chemotherapy due to its high toxicity and consequent dose reductions. Targeted delivery of chemotherapeutic drugs to PDAC cells without affecting healthy no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…In terms of toxicity, Shi et al reported that biodegraded products of MSNs with particle sizes of 420 nm show no obvious toxicity to either MDA-MB-468 cells or COS-7 cells 101 . Various morphologies, shell thicknesses, pore volumes, pore structures, and surface modifications provide distinct characteristics for drug delivery [102][103][104][105] . For instance, Li et al designed persistent luminant nanoparticles (PLNPs) with MSNs as templates 106 .…”
Section: Mesoporous Silicamentioning
confidence: 99%
“…In terms of toxicity, Shi et al reported that biodegraded products of MSNs with particle sizes of 420 nm show no obvious toxicity to either MDA-MB-468 cells or COS-7 cells 101 . Various morphologies, shell thicknesses, pore volumes, pore structures, and surface modifications provide distinct characteristics for drug delivery [102][103][104][105] . For instance, Li et al designed persistent luminant nanoparticles (PLNPs) with MSNs as templates 106 .…”
Section: Mesoporous Silicamentioning
confidence: 99%
“…Using mesoporous silica nanoparticles for drug delivery faces the problem of continuous drug release, which can be overcome by using various sealing strategies (the so called "caps" or "gate keepers"). 80,81 For this reason, mesoporous silica NPs drug carriers are less advanced in clinical studies although they proved to be very efficient drug carriers. For the specific case of nanoparticles as carriers for Irinotecan, a rather limited number of clinical trials are reported (for example see 82,83 ).…”
Section: D Image Reconstruction and Nps Incorporationmentioning
confidence: 99%
“…Over the last decade, the use of nanocarriers to minimize the side effects of available anticancer drugs and improve therapeutic effect has attracted significant attention. Various nanostructures have been explored as drug carriers, such as liposomes, polymeric nanoparticles, nanogels, mesoporous silica nanoparticles, carbon nanotubes, quantum dots, and magnetic nanoparticles 5–7 . Magnetic nanoparticles (MNs), especially iron oxide nanoparticles (IONPs) have excellent hydrophilicity, biocompatibility, small particle size, low toxicity and unique superparamagnetic properties and have been most widely investigated in the medical fields, such as drug delivery, hyperthermia treatment, and magnetic resonance imaging 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Various nanostructures have been explored as drug carriers, such as liposomes, polymeric nanoparticles, nanogels, mesoporous silica nanoparticles, carbon nanotubes, quantum dots, and magnetic nanoparticles. [5][6][7] Magnetic nanoparticles (MNs), especially iron oxide nanoparticles (IONPs) have excellent hydrophilicity, biocompatibility, small particle size, low toxicity and unique superparamagnetic properties and have been most widely investigated in the medical fields, such as drug delivery, hyperthermia treatment, and magnetic resonance imaging. 8,9 However, due to the large surface-to-volume ratio and magnetic dipole-dipole interaction, IONPs tend to agglomerate, which leads to a significant reduction of their circulation time in the body.…”
mentioning
confidence: 99%